1999
DOI: 10.1074/jbc.274.17.11693
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T Cell Signaling by Mitogen-activated Protein Kinase-targeted Hematopoietic Tyrosine Phosphatase (HePTP)

Abstract: Activation of T lymphocytes to produce cytokines is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
151
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 136 publications
(166 citation statements)
references
References 48 publications
10
151
0
Order By: Relevance
“…When transiently overexpressed in Jurkat or 293 cells, HePTP is associated with ERK even in the absence of stimulation. 11,12 In our stable K562 cell lines, however, we have not observed constitutive association of HePTP with ERK2, which might be explained by lower expression levels as compared to transient transfections. To further investigate the association of HePTP with ERK2 we therefore used transient transfection of 293 cells (Figure 3b).…”
Section: Inhibition Of Heptp Enhances Nuclear Translocation Of Erkmentioning
confidence: 53%
See 4 more Smart Citations
“…When transiently overexpressed in Jurkat or 293 cells, HePTP is associated with ERK even in the absence of stimulation. 11,12 In our stable K562 cell lines, however, we have not observed constitutive association of HePTP with ERK2, which might be explained by lower expression levels as compared to transient transfections. To further investigate the association of HePTP with ERK2 we therefore used transient transfection of 293 cells (Figure 3b).…”
Section: Inhibition Of Heptp Enhances Nuclear Translocation Of Erkmentioning
confidence: 53%
“…HePTP contains two consensus ERK phosphorylation sites (T45 and S72) adjacent to the KIM motif and Saxena et al 11 recently suggested that phosphorylation of these sites might interfere with the binding of HePTP to its substrates. Therefore we asked if such a mechanism could explain our observation that ectopic expression of wild-type HePTP has no significant effect on the nuclear translocation of ERK2 in PMA-treated K562 cells (see Figure 3a).…”
Section: Inhibition Of Heptp Enhances Nuclear Translocation Of Erkmentioning
confidence: 99%
See 3 more Smart Citations